2018
DOI: 10.2217/cer-2018-0040
|View full text |Cite
|
Sign up to set email alerts
|

Cost impact of the transitional care model for hospitalized cognitively impaired older adults

Abstract: These findings suggest that the Transitional Care Model can reduce both the amount of other postacute care and the total cost of care compared with alternative services for cognitively impaired older adults. Clinicaltrials.gov : NCT00294307.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
17
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 43 publications
0
17
0
Order By: Relevance
“…Authorisation problems between nurses and physicians regarding who is responsible and accountable for healthcare provision are a challenge to developing quality transitional care programmes (38, 42). Transitional care interventions for older patients can be cost‐effective, but are dependent on management effectiveness of sufficient staff provision and equipment (46, 47). Considering these multiple stress factors, it is important to provide continuous support to primary and community health nurses to prevent burnout and high staff turnover rates as well as improve patient‐related communication mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…Authorisation problems between nurses and physicians regarding who is responsible and accountable for healthcare provision are a challenge to developing quality transitional care programmes (38, 42). Transitional care interventions for older patients can be cost‐effective, but are dependent on management effectiveness of sufficient staff provision and equipment (46, 47). Considering these multiple stress factors, it is important to provide continuous support to primary and community health nurses to prevent burnout and high staff turnover rates as well as improve patient‐related communication mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…The reduction of adverse events has also been related to interventions with a multidisciplinary approach as well as communication between health professionals during the transition from patient to home [ 24 ]. The Transitional Care Model (TCM), a multicomponent, nurse-led intervention has been tested in the U.S. and has consistently shown that the intervention which is provided on average for 60 days (range 1–3 months) can increase time to first re-hospitalization or death, decrease the number of hospitalization readmissions and number of days hospitalized, decrease costs and improve patient reported outcomes [ 17 , 25 27 ]. The TCM features a hospital to community dwelling intervention with nine core components.…”
Section: Introductionmentioning
confidence: 99%
“…Among the studies on hospital readmission, some common characteristics among patients were identified. Among the most common pathologies, cardiovascular diseases [17][18][19][20][21] and Chronic Obstructive Pulmonary Disease (COPD) stand out.21,22 In addition, some articles selected elderly patients [23][24][25] and with LACE score (predictive readmission score) in their samples greater than or equal to ten 26 .…”
Section: Resultsmentioning
confidence: 99%